Assessing Psychometric Properties of Malaysian Secondary School Students’ Arabic Vocabulary Knowledge Inventory - Zunita Mohamad Maskor; Harun Baharudin (Global Journal Al-Thaqafah, 2024)
This study examines the use of psychometric properties to measure the Arabic vocabulary knowledge of Islamic secondary school students in Malaysia. An instrument was developed as a diagnostic test to measure various dimensions of Arabic vocabulary knowledge based on the Rasch Model. The study may give insight into the depth of Malaysian secondary school students’ understanding of Arabic language in word meaning. This paper also discusses the development of the Arabic Vocabulary Knowledge Inventory (PekkA). The instrument consisted of 57 items of vocabulary knowledge that focused on the aspects of meaning namely denotative meaning, semantic relationship, word formation, and word combination. 483 respondents were randomly selected from 39 Islamic secondary schools in Peninsular Malaysia. The study employed a crosssectional quantitative research design. The data was analyzed using the WINSTEP, a Rasch Measurement Model software to determine the validity and reliability of the instrument. The result of the study confirmed the psychometric requirement by Rasch model with good reliability and validity. In general, the results suggest that the instrument could be used as a reliable research instrument for evaluating the vocabulary knowledge among Arabic language learners in secondary school settings.